THE FORMATION OF UZBEK STAGE ART AND THE HISTORICAL ACTIVITIES OF ITS PROMINENT REPRESENTATIVES - Murtazova S.B.; Nomozova M.A (TADQIQOTLAR, 2025)
Abstract: This article summarizes the history of the introduction and formation of  variety  art  in  Uzbekistan,  as  well  as  the  historical  activities  of  its  prominent representatives.  Moreover,  facts  related  to  the  repertoire  of  outstanding  figures  in Uzbek variety art have been analyzed.